MicroRNA-467g inhibits new bone regeneration by targeting Ihh/Runx-2 signaling. (April 2017) - Kureel, Jyoti; John, Aijaz A; Dixit, Manisha; Singh, Divya
Highlights: The role of miR-467g is not known in the regulation of osteoblast functions. MiR-467g inhibits osteoblast functions and directly targets Runx-2 and Hhip genes to regulate osteogenesis. MiR-467g inhibits new bone regeneration by negatively regulating Ihh/Runx-2 signaling pathway. Therapeutic approaches targeting miR-467g could be useful in enhancing the new bone formation and treatment of pathological conditions of bone loss. Abstract: MicroRNAs are important post transcriptional regulators of gene expression and play critical role in osteoblast differentiation. In this study we report miR-467g, an uncharacterized novel miRNA, in regulation of osteoblast functions. Over-expression of miR-467g inhibited osteoblast differentiation. Target prediction analysis tools and experimental validation by luciferase 3′ UTR reporter assay identified Runx-2 as a direct target of miR-467g. Over expression of miR-467g in osteoblasts down regulated Runx-2 and Ihh signaling components. Furthermore, silencing of miR-467g was done to see its role in Ihh and Runx-2 mediated bone healing and regeneration in a drill hole injury model in BALB/c mice. Silencing of miR-467g led to significant increase in new bone regeneration and Ihh and Runx-2 localization at injury site in a day dependent manner. In conclusion, miR-467g negatively regulates osteogenesis by targeting Ihh/Runx-2 signaling. We, thus, propose that therapeutic approaches targeting miR-467g could be useful in enhancing the new bone formation.